The Use of Primary Source Material in Academic Research: A View from Cambridge Archive Editions - Jessica Lagan (Сравнительная политика, 2015)
The article analyses the possibility of using historical sources (and above all primary sources) in political science research. Particularly, the author provides specific examples of archive documents to prove the thesis that history is grounded in politics and governance.